OP0250 A randomised, double-blind study to assess the safety, tolerability and preliminary efficacy of leniolisib (CDZ173) in patients with primary sjÖgren's syndrome. (12th June 2018) - Dörner, T.; Zeher, M.; Laessing, U.; Chaperon, F.; De Buck, S.; Hasselberg, A.; Valentin, M.-A.; Ma, S.; Cabanski, M.; Kalis, C.; Burkhart, C.; Gergely, P.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a systemic and progressive autoimmune disease characterised by lymphoid infiltration and progressive alteration of exocrine glands secretory function. Ectopic germinal center-like structures harbour plasma cells that generate autoantibodies leading to immune complex formation. Leniolisib (CDZ173) is an oral low molecular weight compound that selectively inhibits the lipid kinase PI3Kδ. In animals, leniolisib blocks PI3Kδ-dependent B cell functions, disrupts germinal centre formation and immune cell trafficking, supporting the rationale for a PI3Kδ–targeted therapy in pSS Objectives: To evaluate the safety, tolerability, pharmacokinetics (PK) and preliminary clinical efficacy of multiple oral doses of leniolisib, after 12 weeks of treatment, in pSS patients Methods: Double-blind, randomised, placebo-controlled, parallel-design study recruited 30 seropositive pSS patients with moderate to severe disease activity as determined by EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI)≥6, EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI)≥5 and stimulated whole salivary flow rate >0 mL/min. Patients were randomised in a 2:1 ratio to receive leniolisib (70 mg b.i.d) or placebo. The primary outcome was change in ESSPRI at week 12. Secondary outcomes included PK, changes in ESSDAI, the Short Form-36 (SF-36), Multidimensional Fatigue Inventory (MFI) and global Visual Analogue Scales (VAS) completed by patients and physicians. Additional assessments included lacrimal gland function and biomarkers relevant to pathway and disease Results: Overall safety and tolerability profile of leniolisib was acceptable, but appeared less favourable than placebo. In particular, rash occurred more frequently in the leniolisib group (11/20 patients) compared to placebo (1/10 patients). There was a slight improvement (not statistically significant) in ESSPRI scores (dryness, pain and fatigue) favouring leniolisib. Similar trends were observed in secondary endpoints (SF-36/mental and physical, MFI, VAS completed by patients and physicians). After 12 weeks of treatment, there was a slight improvement (not statistically significant) in the lacrimal gland function in the leniolisib group compared to placebo. The observed PK profile was as expected based on healthy volunteer data. Biomarker results suggest a strong and sustained target and pathway engagement, as evidenced by inhibition of phosphorylated Akt in ex-vivo stimulated B cells, significant decrease in serum CXCL13 and reduced frequency of circulating Follicular T helper-like cells. There was a trend of decreasing autoantibody levels in leniolisib-treated patients Conclusions: Leniolisib had an acceptable safety and tolerability profile, but caused rashes a known class effect of PI3K inhibitors. Target and pathway engagement were confirmed, however no clear efficacy signal for leniolisib was seen based on ESSPRI and ESSDAI in this Proof-of-Concept study at the studied dose. Disclosure of Interest: T. Dörner: None declared, M. Zeher: None declared, U. Laessing: None declared, F. Chaperon: None declared, S. De Buck: None declared, A. Hasselberg: None declared, M.-A. Valentin Shareholder of: Novartis stock option, Employee of: Novartis, S. Ma: None declared, M. Cabanski: None declared, C. Kalis: None declared, C. Burkhart: None declared, P. Gergely: None declared